Potentiality of Bambusa, Phyllostachys and Urochloa species to vegetate degraded areas - Cibele Dutra de França; Joilson Sodré Filho (Pesquisa Florestal Brasileira)
Bamboos and forage grasses (Poaceae) can be used as recovery plants in degraded tropical areas, because of their fast plant growth and dense root systems. This study evaluated the survival, growth and dry matter production of four bamboo species (Bambusa gracilis, Bambusa vulgaris, Phyllostachys aurea and Phyllostachys sp.) and one forage grass (Urochloa decumbens) in two substrates. The experiment was established in a completely randomized design: 5 × 2 factorial scheme, with five recovery plants and two substrates (chemical or organic), with five replicates. Seedlings survival and several root growth parameters were evaluated at 60, 120 and 180 days after planting. Organic substrate increased the survival of the recovery plants compared to the chemical one. Phyllostachys aurea produced the highest root dry matter, surface area and volume of roots and U. decumbens also showed the highest length and the same root growth parameters. The maximum length of thin roots was observed in Phyllostachys sp. and in B. vulgaris. The studied species are recommended as recovering plants in degraded areas, due to their high incidence of thin roots in larger proportions than thick roots.